Clinical Presentation, Management, and Outcomes of Primary Hyperparathyroidism during Pregnancy. (25th September 2017) - Hu, Ya; Cui, Ming; Sun, Zhengyi; Su, Zhe; Gao, Xiang; Liao, Quan; Zhao, Yupei
Abstract : Background . Primary hyperparathyroidism (pHPT) in pregnancy is a rare event, but it poses a significant risk to mothers and fetuses. The optimal treatment strategy remains controversial. Methods . We present a consecutive series of twelve pregnant women with pHPT. Results . Twelve women were diagnosed with pHPT during pregnancy or in the postpartum period. Four of them presented no symptoms or mild symptoms. Four patients experienced serious complications, including hypercalcaemic crisis, acute pancreatitis, and eclampsia. Another four patients were identified postpartum as the result of neonatal convulsion with hypocalcaemia. Minimally invasive parathyroidectomy (MIP) under cervical plexus block was successfully performed in 11 of them during pregnancy or postpartum. The serum levels of ionized calcium and intact parathyroid hormone (iPTH) were much higher in patients with severe complications in this cohort than those in the group of patients with no symptoms or mild symptoms and patients who were diagnosed postpartum. Conclusions . MIP under cervical plexus block might be a safe and effective treatment for pregnant women with pHPT. Even though both conservative and surgical treatments are applicable for most mothers and fetuses with asymptomatic and mild hyperparathyroidism, serious complications may have catastrophic consequences for both.